Can International Macroeconomic Models Explain Low-Frequency Movements of Real Exchange Rates? - Rabanal, Pau (IMF Working Papers; Working Paper, 2012)
Real exchange rates exhibit important low-frequency fluctuations. This makes the analysis of real exchange rates at all frequencies a more sound exercise than the typical business cycle one, which compares actual and simulated data after the Hodrick-Prescott filter is applied to both. A simple two-country, two-good model, as described in Heathcote and Perri (2002), can explain the volatility of the real exchange rate when all frequencies are studied. The puzzle is that the model generates too much persistence of the real exchange rate instead of too little, as the business cycle analysis asserts. Finally, we show that the introduction of adjustment costs in production and in portfolio holdings allows us to reconcile theory and this feature of the data.